EFFECT OF LONG FERMENTATION OF DOUGH ON PHYSICAL AND CHEMICAL PROPERTIES OF CRACKERS SUBSTITUTION OF COMPOSITE FLOUR - Titi Mutiara Kiranawati; Ummi Rohajatien; Rahma Safira Jayanti (Jurnal Agroindustri, 2021)
Composite flour is flour made from two foodstuffs, namely Tengger potatoes and moringa leaves. Composite flour can be used as a substitute substitute for wheat flour substitutes for the manufacture of crackers products. Crackers are a type of biscuits that go through the fermentation process. Fermentation aims to maturate the dough, forming a good taste and texture. This study aims to find out ptorein levels, moisture content, free fatty acid content, flowering power, broken power and browning index crackers substitution of composite flour with fermentation duration of 0 hours, 1 hour, and 2 hours. This study is an experimental study using a Complete RandomIzed Design with 3 treatments and two replays. The data was statistically tested using ANOVA and Duncan's Multiple Range Test (DMRT). The results of the analysis showed the long fermentation treatment of dough crackers differed markedly from its chemical properties and physical properties. Crackers with a fermentation time of 2 hours contain the highest protein content of 16.44%, the greatest moisture content of 0.916%, and the lowest free fatty acid content of 0.014%, and physical properties including the highest growth power of 28.237%, the lowest broken power of 0.006N/Cm² and the brownish index of 88.469%.